Determinan Kepatuhan Remaja Putri Tingkat SMA di Kota Ruteng Dalam Mengonsumsi Tablet Fe - Dewi, Imelda Rosniyati; Centis, Maria Choncita Leyla; Trisnawati, Reineldis E E (Universitas Malahayati, 2024)
ABSTRACT Investments in sexual and reproductive health and rights, including for adolescent girls, can provide enormous economic and social returns. WHO recommendations agreed on a global action plan and targets for maternal, infant and child nutrition, with a commitment to halve (50%) the prevalence of anemia in adolescents and WUS by 2025 by prioritizing the provision of TTD through school institutions. The purpose of this study was to determine the determinants of factors affecting adolescents' adherence in consuming Fe. The method used in this study was quantitative-cross sectional with chi-square analysis test involving 80 female students. The test results showed the þ value of the relationship between knowledge and adherence of adolescent girls (0.3), attitudes with adherence of adolescent girls (0.1), and support (family and teachers) with adherence of adolescent girls in consuming Fe (1.0). There is no relationship between knowledge, attitude and support to the compliance of adolescent girls in consuming Fe. Keywords: Adolescent Girls, Adherence, Fe Tablets ABSTRAK Investasi dalam kesehatan dan hak-hak seksual dan reproduksi, termasuk untuk remaja perempuan, dapat memberikan keuntungan ekonomi dan sosial yang sangat besar. Rekomendasi WHO menyepakati rencana aksi dan target global untuk gizi ibu, bayi, dan anak, dengan komitmen mengurangi separuh (50%) prevalensi anemia pada remaja dan WUS pada tahun 2025 dengan memprioritaskan pemberian TTD melalui institusi sekolah. Tujuan penelitian ini adalah untuk mengetahui determinan faktor yang memengaruhi kepatuhan remaja dalam mengonsumsi Fe. Metode yang digunakan dalam penelitian ini adalah kuantitatif-cross sectional dengan uji analisis chi-square yang melibatkan 80 siswi. Hasil uji menunjukkan þ value hubungan pengetahuan dengan kepatuhan remaja putri (0.3), sikap dengan kepatuhan remaja putri (0.1), dan dukungan (keluarga dan guru) dengan kepatuhan remaja putri dalam mengonsumsi Fe (1.0). Tidak ada hubungan antara pengetahuan, sikap dan dukungan terhadap kepatuhan remaja putri dalam mengonsumsi Fe. Kata Kunci: Remaja Putri, Kepatuhan, Tablet Fe